Decreased enteritis resistance ability by dietary low or excess levels of lipids through impairing the intestinal physical and immune barriers function of young grass carp (Ctenopharyngodon idella). Issue 67 (August 2017) - Feng, Lin; Ni, Pei-Jun; Jiang, Wei-Dan; Wu, Pei; Liu, Yang; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhang, Yong-An; Tang, Xu; Shi, He-Qun; et al.
Abstract: The current study explores the hypothesis that low or excess levels of lipids decrease the enteritis resistance ability through impairing the intestinal physical and immune barrier function of young grass carp (Ctenopharyngodon idella) . A total of 540 young grass carp with an average initial weight of 261.41 ± 0.53 g were fed diets containing six graded levels of lipids at 5.9, 21.4, 36.0, 50.2, 66.6 and 80.1 g/kg for 8 weeks. After that, a challenge trial was conducted by injection of Aeromonas hydrophila over 2 weeks. The results show that compared with optimal lipids level, low or excess levels of lipids impair fish immune barrier function through declining humoral compounds and down-regulating the mRNA levels of interleukin 4/13A (IL-4(13)A) [not in the proximal intestine (PI)], IL-4(13)B, IL-6, IL-10, transforming growth factor β1 (TGF-β1), inhibitor of κBα (IκBα), TOR and ribosomal p70S6 kinase (S6K1) ( P  < 0.05), and up-regulating tumor necrosis factor α (TNF-α), interferon γ2 (IFN-γ2), IL-1β, IL-8, IL-12 p40 (not p35), nuclear factor κB p65 (NF-κB p65), IκB kinase α (IKKα), IKKβ, IKKγ, and eIF4E-binding protein (4EBP) in the intestine of young grass carp ( P  < 0.05). In addition, low or excess levels of lipids also decrease young grass carp physical barrier function through down-regulating the mRNA levels of zonula occludens (ZO-1), ZO-2b [only in the distal intestine (DI)], Claudin b, c, 3, 12, 15a, 15b (only in the DI), 7b (not 7a) and Occludin by MAPKK 6/p38 MAPK (not JNK)/MLCK signaling molecules, down-regulating B-cell lymphoma-2 (Bcl-2) and inhibitor of apoptosis protein (IAP) and up-regulating the mRNA levels of apoptotic protease activating factor-1 (Apaf-1), Caspase-3, -8 and -9 and Fas ligand (FasL) (not in the DI), and decreasing antioxidant ability via Kelch-like ECH-associating protein 1 (Keap1)/NF-E2-related factor 2 (Nrf2) signaling molecules in the intestine. Based on the quadratic regression analysis for the enteritis resistance ability, LA activities and GSH content in the MI were established to be 54.5, 49.91 and 47.83 g lipid/kg diets, respectively. Highlights: Low and excess levels of lipids decrease fish intestinal immune barrier function. Low and excess levels of lipids impair fish intestinal physical barrier function. Low and excess levels of lipids decrease enteritis resistance ability of fish. Lipids regulate fish intestinal NF-κB, TOR, Nrf2, apoptosis and MLCK signaling.